Cancers prevented in Australia in 2010 through the consumption of aspirin - Louise F. Wilson; Adele C. Green; Bradley J. Kendall; Susan J. Jordan; Christina M. Nagle; Christopher J. Bain; Rachel E. Neale; David C. Whiteman (Australian and New Zealand Journal of Public Health, 2015)
Abstract Objectives: To estimate the proportion and number of cancers in Australia in 2010 that may have been prevented from occurring due to daily use of aspirin in the population. Methods: We calculated the Prevented Fraction (PF) of colorectal and oesophageal cancers using standard formulae. The PF is the proportion of the hypothetical total load of cancer in the population that was prevented by exposure to aspirin. The formula incorporates estimates of the prevalence of aspirin use in Australian adult populations, the relative risks associated with aspirin use and cancer incidence. Results: An estimated 335 colorectal cancers, 22 oesophageal adenocarcinomas and 29 oesophageal squamous cell carcinomas (SCC) were potentially prevented due to daily aspirin use. These figures equate to 2.2%, 3.1% and 5.4% of all colorectal cancers, oesophageal adenocarcinomas and oesophageal SCCs, respectively, that would otherwise have occurred but were potentially avoided due to the daily use of aspirin pertaining in the Australian population. Conclusions: At current levels of consumption, a small but measurable reduction in cancer incidence can be attributed to daily aspirin use. Implications: Assuming the benefits outweigh the harms of known gastrointestinal toxicity and other hazards, aspirin use may be considered for some people to prevent the development of particular gastrointestinal cancers.